Analysis of the Implementation of the Village Fund Management Policy during the Covid 19 Pandemic in the Tangerang District, Banten Province - Gatot Tri Suryanta; Khasan Effendy; Mansyur Achmad; Sampara Lukman (Budapest International Research and Critics University, 2022)
The problem of distributing Village Fund Direct Cash Assistance during the COVID-19 pandemic in Tangerang Regency was not yet on target because there were still overlapping regulatory rules from the central government and the data collection system for aid recipients had not been transparent, making it difficult for the village government to collect data on Village Fund Cash Direct Aid recipients. The theory used Using the Policy Implementation theory according to Grindle (1980) states: